A concise history of economists' assumptions about markets from Adam Smith to Joseph Schumpeter - Mitchell, Robert Edward (Praeger, 2014)
"This open-minded, multidisciplinary approach challenges existing world views on the endogenous and exogenous forces that drive markets and economies"--